The Influence of Socio-Demographic Characteristics of Fiji Dairy Farmers on their Climate Change Adaptation - Igbal, Mohammed Rasheed; Iqbaal, Ubaadah Bin; Bibi, Fazleen Farhat; Magiri, Royford Bundi (Journal of Cultural Analysis and Social Change, 2025)
Climate change is the biggest threat to the dairy industry and the agricultural sector, particularly in the small and developing country like Fiji. Fiji is one of the countries where dairy farmers contribute a lot to the economy and make it run by providing quality milk. The influence of socio-demographic characteristics on climate adaptation is vital for developing strategies that support dairy farmers in adapting to climate change. All know the importance of dairy farmers in Fiji as milk is the most usable product sold in every house in Fiji. People count it as a need for themselves, and the babies need it the most. However, when the price fluctuates in the market, it directly affects the dairy farmers back in the villages. They are happier to export milk or milk products such as cheese and yogurt as from that the milk production factories make a profit and so the dairy farmers back in the village. This study investigates the influence of socio-demographic characteristics of Fiji such as gender, age, ethnicity, education level, income, location, etc, and its dairy farmers, and how dairy farmers adapt to climate change. The importance of dairy farming in Fiji. Following with how farmers adapt to the climate change methods will also be discussed in this study together with the effects of climate change on the dairy industry/farmers. Overall, the study will highlight the importance of dairy farming in Fiji and the importance of considering the socio-demographic characteristics of dairy farmers, when developing the climate change adaptation methods in Fiji. When one understands the factors that influence the adaptation methods of climate change, the government or NGOs can develop their targeted interventions to help support all dairy farmers in adapting to climate change, at the same time maintaining the sustainability of the dairy industry in Fiji..